2016
DOI: 10.1515/tjb-2016-0018
|View full text |Cite
|
Sign up to set email alerts
|

The effects of crocin (active contstituent of saffron) treatment on brain antioxidant enzyme mRNA levels in diabetic rats / Diyabetik ratlarda safranın aktif içeriği olan krosin tedavisinin beyindeki antioksidan enzimlerin mRNA seviyeleri üzerine etkisi

Abstract: Objective: The aim of the present study is to evaluate the effect of crocin on mRNA expression of antioxidant enzymes, SOD, CAT and GPX in the brain of the STZ induced diabetic rats.Methods: Thirty animals randomized in three groups containing ten animals in each group as follows; control (non-diabetic rats), DM (STZ-induced untreated diabetic rats), DM+crocin (STZ-induced diabetic rats treated with crocin,). Crocin was given at a dose of 20 mg/kg bw/day by gavage for 21 days.Results: STZ injection caused a si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Also, Altınöz et al demonstrated that consumption of crocin at the dose of 20 mg/kg for 21 days could modulate mRNA expression of antioxidant enzymes (CAT, GPX, and SOD). Further consumption of crocin can treat the STZ-induced oxidative stress in the brain of diabetic rats (19). The radical scavenging activity of crocin has also been shown in several in vitro models (20).…”
Section: Discussionmentioning
confidence: 94%
“…Also, Altınöz et al demonstrated that consumption of crocin at the dose of 20 mg/kg for 21 days could modulate mRNA expression of antioxidant enzymes (CAT, GPX, and SOD). Further consumption of crocin can treat the STZ-induced oxidative stress in the brain of diabetic rats (19). The radical scavenging activity of crocin has also been shown in several in vitro models (20).…”
Section: Discussionmentioning
confidence: 94%